A study of private equity rounds of entrepreneurial finance in EU: Are buyout funds uninvited guests for startup ecosystems? - Hiroyuki Miyamoto; Cristian Mejia; Yuya Kajikawa (Journal of Risk and Financial Management, 2022)
This paper studies the difference between startup investments by private equity funds (buyout funds; PE) and venture capital funds (VC). PEs, which have traditionally invested in mature companies, have been increasingly investing in later-stage startups in recent years. Based on Crunchbase's data on EU startup investments from 2011 to the first half of 2021, we find that: (1) later-stage VC-backed startups and PE-backed startups differ in terms of the industry domain, (2) PE-backed startups tend to have higher revenue when they receive investments, and (3) VC-backed startups are more likely to exit via Initial Public Offering (IPO) and slightly less likely to exit via Mergers and Acquisitions (M&A) than PE-backed startups. These results connect previous studies on VC and PE and deepen our understanding of later-stage startup investment. It also suggests that PE invests differently than VCs and provides new added value to the startup ecosystem. In addition, it adds insights into corporate behavior in new business domain expansion.
Keywords: 650; buyout fund; entrepreneurial finance; private equity; startups; venture capital